A full sequence impedance modelling and stability analysis of the virtual synchronous generator with inner loops. Issue 2 (12th January 2021) - Peng, Yang; Wang, Yue; Liu, Yonghui; Yu, Peng; Shu, Sirui; Lei, Wanjun
Abstract: Virtual synchronous generator (VSG) has been widely studied owing to its inertia support to the grid. However, the stability of VSG is not analysed accurately for actual applications in previous studies that overlook voltage and current inner loops of VSG. Since inner loops are essential to control output voltage and current accurately in practical engineering, this study focuses on stability analysis of the interconnection system of VSG and the grid by sequence impedance modelling of VSG with inner loops. The complete sequence impedance model for VSG with inner loops is built and compared with that of the VSG‐ignoring inner loops, and then the stability is analysed based on that. It shows that inner loops bring the risk of instability and oscillation for VSG, which was not predicted in previous studies. Then, the influence of each parameter of inner loops on the impedance and oscillation is analysed, showing that the oscillation can hardly be eliminated by tuning the parameters of inner loops. Therefore, corresponding virtual resistor with proper value is studied and adopted in VSG with inner loops to avoid oscillation. Finally, the correctness of theoretical analysis and the effectiveness of the adopted virtual resistance are verified by the hardware‐in‐the‐loop experiments.